Encounters with God in Augustine's Confessions : books VII-IX - Vaught, Carl G., 1939- (State University of New York, 2004)
This reappraisal of the middle section of Augustine's Confessions covers the period of Augustine's conversion to Christianity. The author argues against the prevailing Neoplatonic interpretation of Augustine.
Keywords: Augustine, -- of Hippo, Saint, -- 354-430. -- Confessiones.; Augustine, -- of Hippo, Saint, -- 354-430.; Augustine, -- of Hippo, Saint, -- 354-430; Confessiones (Augustine, of Hippo, Saint); Spirituality -- Christianity -- History -- Early church, ca. 30-600.; Christian saints -- Algeria -- Hippo (Extinct city) -- Biography -- History and criticism.; Saints chrétiens -- Algérie -- Hippone (Ville ancienne) -- Biographies -- Histoire et critique.; RELIGION -- Christian Church -- History.; RELIGION -- Christianity -- History.; Christian saints; Spirituality -- Christianity -- Early church; Algeria -- Hippo (Extinct city); 30-600; Biographies; Criticism, interpretation, etc.; History